Pengaruh Pengetahuan Perpajakan, Kesadaran Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak - Cecylya Thancy; Rudi Syafputra; Dian Puji Puspita Sari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Increasing taxpayer compliance cannot be separated from Tax Knowledge. Taxpayer compliance can increase state revenues from the tax sector. Taxpayers must understand knowledge about taxation in general and tax procedures. This type of research is quantitative with primary data sources obtained by distributing questionnaires to the population in the research of individual taxpayers at KPP Pratama Pekanbaru Tampan. Test tools in research use validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of research on tax knowledge partially influence taxpayer compliance.